Development and characterization of a new multi-strength level binder system using soda residue-carbide slag as composite activator. (12th July 2021) - Guo, Weichao; Zhang, Zhaoyun; Bai, Yanying; Zhao, Guanqun; Sang, Zhaohu; Zhao, Qingxin
Highlights: A new composite alkali activator is prepared by mixing soda residue and carbide slag. A new multi-strength level binder system with strength of 17.5–43.2 MPa is prepared. CS can enhance the chloride ion consolidation rate and reduce the drying shrinkage. FA can adjust the strength and reduce the drying shrinkage, also reducing the cost. The new binder system can replace Portland cement to prepare unreinforced concrete. Abstract: A new multi-strength level binder system was developed as a potential replacement of cement. It utilized alkaline solid wastes soda residue (SR) and calcium carbide slag (CS), to synergistically activate ground granulated blast-furnace slag (GGBS) and fly ash (FA). A comprehensive combination of experimental studies on compressive strength, setting time, fluidity, chloride-ion consolidation, and drying shrinkage with XRD, TG-DTG, FTIR and SEM-EDS examinations ensured a systematic evaluation of properties and evolution mechanism of the proposed binder. The results show that mixing CS can increase the early hydration rate and generate more C-S-H gel and Friedel's salt, Hydrotalcite crystal products. As a result, the early and late strengths were significantly improved. The chloride-ion consolidation rate was increased, and the drying shrinkage was reduced. On the other hand, FA's low activity was used to adjust the strength level. Also the FA can reduce shrinkage, but it hindered the consolidation of chloride ions. The new binder system had a 28d strength of 17.5–43.2 MPa, with the initial and final setting times of 3.8–6.1 h and 6.4–10.2 h, respectively. At the water-to-binder ratio of 0.5, the mortar's fluidity was 146–181 mm, the drying shrinkage was 0.11%–0.29%, and the chloride ion consolidation rate exceeded 70%. This new binder system can be applied to concrete blocks, pavement bricks, slope protection concrete, and other unreinforced products. The results obtained are instrumental in mitigating the environmental pollution caused by industrial solid wastes and reducing binders' cost.